2022
DOI: 10.1055/a-1725-8653
|View full text |Cite
|
Sign up to set email alerts
|

Wirksamkeit eines Adipositastherapieprogramms bei Kindern und Jugendlichen in der Routineversorgung

Abstract: ZusammenfassungAktuelle Therapiestudien zu Übergewicht und Adipositas im Kindes- und Jugendalter berichten häufig einzelne psychologische oder somatische Parameter. In der vorliegenden Studie wurde die Wirksamkeit einer multimodalen Adipositastherapie in der ambulanten Routineversorgung über 12 Monate bei N=278 Kindern und Jugendlichen (Alter 2–17 Jahre) anhand umfassender psychologischer und somatischer Paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, international systematic reviews have shown that randomized controlled studies on multimodal obesity treatments for children and adolescents are only moderately efficacious [ 6 , 7 ]. Additionally, in the outpatient routine care context, multimodal obesity treatments for children and adolescents face challenges, resulting in reduced weight loss effects [ 8 ], uncertain long-term treatment effects [ 6 , 7 ], and high dropout rates [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, international systematic reviews have shown that randomized controlled studies on multimodal obesity treatments for children and adolescents are only moderately efficacious [ 6 , 7 ]. Additionally, in the outpatient routine care context, multimodal obesity treatments for children and adolescents face challenges, resulting in reduced weight loss effects [ 8 ], uncertain long-term treatment effects [ 6 , 7 ], and high dropout rates [ 9 ].…”
Section: Introductionmentioning
confidence: 99%